Initiating Interreligious Tolerance in A Phygital Neighborhood: Reflecting from The Activism of Young Interfaith Peacemaker Community-Indonesia - Mila, Suryaningsi (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: This research explores models of interreligious tolerance within the phygital neighborhood as practiced by the Young Interfaith Peacemaker Community. In collecting research data, I employ qualitative methods through a phenomenology approach by conducting interviews and observation on websites and social medias such as Instagram of the Young Interfaith Peacemaker Community â€“ Indonesia. From this research, I found that YICP campaigned for peace and tolerance through physical and digital neighborhoods. YIPC is enthusiastic about promoting a peace generation through young peacemakers. Interestingly, YIPC has consciously been involved in the theological, spiritual, dialogue of action and dialogue of life as well as conducting a holistic dialogue through the dialogue of head, dialogue of heart, dialogue of hands, and dialogue of holiness. Those models of dialogue can be seen through the activism of YIPC, such as youth peace camps, peace forums, book reviews, scriptural reasoning, visits to places of worship, peace campaigns on social media, and various other peaceful actions. These activities take place on physical and digital platforms. YIPC also created peaceful dialogue, practicing true tolerance by caring interreligious friendship. In the phygital neighborhood, interreligious tolerance should employ the virtues of interreligious dialogue, such as humility, openness, commitment, interconnection or commonality, acceptance, hospitality, mutual understanding, hospitality, and the possibility of mutual growth and change.Â Keywords: Interreligious Dialogue; Interreligious Tolerance; Phygital Neighborhood; YIPC.